Uncontrolled VS. controlled administration of the SSHA - Mote, Jr., Thomas A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A group of 250 undergraduate and graduate students at St. Mary’s University participated in an investigation of the practicability of administering the Survey of Study Habits and Attitudes (Brown & Holtzman, 1967), under uncontrolled conditions. A control group of 122 students completed the SSHA under standard testing conditions and an experimental group of 128 students was given the testing packet and asked to return it upon completion. No significant difference was found between the SSHA scores of the control group and the 48 experimental group members who returned completed forms. It is suggested that the SSHA may be used with some confidence under conditions where it is inconvenient to administer it in the usual manner.